PENGARUH PEMANFAATAN AIR EKSTRAKSI ECENG GONDOK TERHADAP KUAT TEKAN BETON K-175 - Setiobudi, Agus; Purwanto, Herry; Adiguna, Adiguna (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2023)
This study aims to determine the compressive strength value of K-175 concrete with variations in theaddition of water hyacinth extraction water. The research method used was a laboratory experiment, bydetermining the cement water factor and the composition of the new mixture. In this study, 24 cube testobjects were made using variation of water hyacinth extrac mixtures of 1%, 3% and 5%. The results of thisstudy were the compressive strength value of the average normal K-175 concrete at the age of 14 and28days the compressive strength results were 144.3 kg/cm2 and 184.3 kg/cm2, while the compressive strengthwith variations in the addition of 1% water hyacinth extraction water was of 154.8 kg/cm2 and196.4 kg/cm2, variations in the addition of 3% water hyacinth extraction water was 164.7 kg/cm2 and212.3 kg/cm2, while for variations in the addition of 5% was 149.6 kg/cm2 and 193.4 kg/cm2. The optimumcompressive strength obtained in this study was the variation of 3% water hyacinth extracti mixture for theage for 28 days of age, which was 212.3 kg/cm2.